Molecular characterization and in vitro conservation of taro (Colocasia esculenta (L.)Schott) - Sreevidya, M R (Department of Plant Biotechnology, College of Agriculture, 2017)
The study entitled "Molecular characterization and in vitro conservation of taro (Colocasia esculenta (L.) Schott)" was carried out in the Division of Crop Improvement, ICAR – Central Tuber Crops Research Institute, Sreekariyam, Thiruvananthapuram during the period 2016-17. The main objective of the study was to analyze the genetic diversity of taro (Colocasia esculenta) using SSR markers and to maintain them in slow growth conditions for medium term conservation. 36 taro accessions comprising germplasm from various parts of the country, varieties and breeding lines were collected from the taro germplasm maintained at ICAR – CTCRI for molecular characterization and in vitro studies. Good quality and pure DNA was isolated from the selected 36 taro accessions by modified Sharma, et al. (2008) protocol. The quantity of the DNA obtained ranged from 372ng (Line 11) to 2285 ng/μl (DT 1) and the OD values were also good ranging from 0.050 (C-717) to 0.457 (NEH 21). 10 SSR markers were selected for the study, eight from the Uq series (Mace and Godwin, 2002) and two from the Ce1 series (Noyer et al., 2004). The annealing temperatures of these 10 primers were standardized using gradient PCR and ranged from 60 to 68oC. PCR amplified SSR amplicons were resolved in 6% PAGE and 4% high resolution agarose gel electrophoresis. Since, both methods of electrophoresis gave similar results, 4% agarose gel electrophoresis was adopted for further resolution of amplicons from the rest of the primers as it was less cumbersome. The bands obtained were scored as '0','1' based on the presence (1) or absence (0) of bands for further statistical analysis. The SSR primers were found to be highly polymorphic across the 36 accessions and was explained by parameters like Shannon’s diversity index which ranged from 0.88 to 2.09, average number of alleles per locus which ranged from 1.81 to 2.67 and polymorphism information content which ranged from 0.58 to 0.80. The 36 accessions were found to be diverse which was explained by the heterozygosity value (He) which ranged from 0.65 to 0.82. Jaccard’s coefficient was used in NTSys – PC to generate 2 main clusters, I and II. Cluster II had 4 sub clusters. The clustering was not on the basis of geographical similarities as the NEH series which are having geographical similarity were found in different clusters. Common ancestry was also explained when some breeding lines were found in a single cluster. The maximum similarity was found to be 83% between C-557 and NEH 8; NEH 32 and Line 4 as well as Lines 29 and 33. This explained that all the accessions were divergent and there were no duplicates in the set of 36 accessions studied. The main aim of in vitro conservation of taro was to develop an in vitro active genebank of taro and to augment the existing IVAG of tuber crops at ICAR – CTCRI. Apart from conservation, a multiple shoot induction step was incorporated so that rare genotypes present in germplasm or mutants, if present, could be multiplied first before being conserved in the slow growth media. The sprouts from the cormels were taken as explants. The explants were sterilized by keeping in bavistin for 25 min, labolene for 10 min and in HgCl2 for 5 min. They were inoculated in basal MS medium for the establishment of contamination free cultures. The shoot multiplication medium was standardized using six sets of media. Two out of these six media were selected. The best media was MS+TDZ (0.1mg/l) which produced an average of 1.96 multiple shoots and the second best was MS+K (1mg/l) which gave on an average, 1.24 multiple shoots. These cultures were further inoculated into slow growth media, full and half strength MS having 2% sucrose and 2% mannitol. Presence of Mannitol though induced slow growth, explants dried after a few days of inoculation. As a result, for slow growth, full and half strength MS having 2% sucrose was used. Of these two media, half strength MS was found to be more effective in achieving slow growth. The cultures were transferred to the IVAG existing in ICAR – CTCRI.